Utilizing GIS to Examine the Relationship Between State Renewable Portfolio Standards and the Adoption of Renewable Energy Technologies - Chelsea Schelly; Jessica Price (ISPRS International Journal of Geo-Information, 2013)
In the United States, there is no comprehensive energy policy at the federal level. To address issues as diverse as climate change, energy security, and economic development, individual states have increasingly implemented Renewable Portfolio Standards (RPSs), which mandate that utility providers include a specified amount of electricity from renewable energy sources in their total energy portfolios. Some states have included incentives for individual energy technologies in their RPS, such as solar electric (also called photovoltaic or PV technology). Here, we use GIS to visualize adoption of RPSs and electricity generation from renewable energy sources in the US and examine changes in renewable electricity and solar electric generation over time with the goal of informing future policies aimed at promoting the adoption of renewable energy technologies.